Sustainability and the future of work and entrepreneurship for the underserved - Rolle, JoAnn 1953-; Crump, Micah E. S. 1964- (Advances in human resources management and organizational development (AHRMOD) book series, 2022)
"This book highlights marginalized labor and entrepreneurial market segments and reviews strategies used to prepare for technology changes globally with the intent to provide a series of recommendation by thought leaders that may aid in growing and sustaining a more inclusive global society.